LIABILITY OF SHIPPING SERVICES DUE TO BREACH OF DAMAGE TO DELIVERY OF GOODS IN CASH ON DELIVERY TRANSACTIONS - Aprilia Azis, Putri Happy; Prima Anggriawan, Teddy (fakultas hukum universitas PGRI Semarang, 2025)
Liability of shipping services in the context of default that occurs due to damage to an item during delivery, especially in Cash On Delivery (COD) transactions, in the current digital era which is increasingly high and the COD payment method is very popular among e-commerce users, especially Shopee. The COD system provides convenience for buyers and sellers, but with this can create legal risks. With the increase in buyers and increased shipping of goods, the risk of damage and loss of goods can also increase, this can cause problems between the sender, shipping service and recipient of the goods. Damage to goods that occurs due to negligence of the shipping service during the shipping process can be called a default. In this case, the shipping company is obliged to be responsible in accordance with the shipping agreement clauses agreed with the seller.